Conditions for reducing non-repayment of loans - O. I. Ditsulenko; E. A. Posnaya; E. Yu. Cherkashina; N. V. Yurchenko (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. In the modern world of banking business, an important area is the procedure for reducing non-repayment of loans, since large volumes of non-returned loan funds entail negative consequences in the financial activities of the bank. Currently, there is competition in the banking sector and banks sometimes offer clients a loan that is not based on the real state of the financial and economic activities of the potential borrower.Goal. Determine the main conditions for reducing loan defaults in order to minimize the risk of loss of profit and bank bankruptcy.Materials and methods. Non-repayment of loans and assessment of the creditworthiness of borrowers are two very closely interrelated concepts. A welldeveloped assessment mechanism allows you to minimize the number of loans issued for which overdue debt has arisen. As part of this mechanism, it is worth special mentioning the verification of documents of a legal entity, since it is the analysis of the presented data that allows us to predict credit risk.Results and discussion. The study proposes new approaches to checking the borrower's creditworthiness in order to reduce credit risk and the volume of unreturned funds to banks. It is proposed, along with the financial statements of corporate clients, to request tax reporting data, since it shows quarterly data, which will allow a more thorough check of the financial condition of a potential borrower.Conclusion. The directions proposed in the study for minimizing the risk of non-repayment of loans by requesting and analyzing tax reporting data will allow the most thorough and correct verification of potential borrowers, thereby reducing the risk of losses.